Skin protective effects of Nannochloropsis gaditana extract on H2O2-stressed human dermal fibroblasts - Letsiou, Sophia; Kalliampakou, Katerina; Gardikis, Konstantinos; Mantecon, Lalia; Infante, Carlos; Chatzikonstantinou, Marianna; Labrou, Nikolaos E.; Flemetakis, Emmanouil (Frontiers in Marine Science, 2017)
Nowadays, there is a huge interest on natural products obtained from marine organisms that can promote the state of health and well-being for humans. Microalgae represent a primary source of bioactive compounds that could be used as functional ingredients in cosmetic formulations. The aim of the present study is to evaluate for the first time, the effects of Nannochloropsis gaditana extract against oxidative stress in human primary fibroblasts so as to investigate the potential applications of it in cosmetics. To gain an insight into the molecular mechanisms of N. gaditana bioactivity, we developed a new RT-qPCR platform for studying transcript accumulation for an array of selected genes (up to 100) involved in many skin-related processes including anti-aging, hydration, oxidative stress response, DNA damage. For the oxidative stress evaluation, H2O2 was used as stressor. The study of the transcript accumulation of genes revealed that N. gaditana extract exhibits skin protection properties by mediating oxidative responses and apoptosis (including SOD1,GPX1,BID), positively regulates genes involves in skin texture and hydration (including AQP3 Col6A1 FBN1) and modulates the expression of genes involved in skin irritation, DNA damage and aging (including IL1R PCNA FOXO3). These findings indicate that the specific N. gaditana extract possesses significant in vitro skin protection activity against induced oxidative stress, and provide new insights into the beneficial role of microalgae bioactive compounds in cosmetic formulations protecting skin from oxidative stress.